Groovy 3 adds support for Java’s lambda syntax expressions. This way we can write code in Groovy using lambda expressions just like in Java. But Groovy adds an additional feature and that is default parameter values for lambda expressions.

In the following example we use a default parameter value for a lambda expression.

// Groovy 3 supports Java's lambda syntax expressions.
def inc = n -> n + 1

assert inc(1) == 2

// But also adds default parameter values.
def multiplyBy = (n, factor = 2) -> n * factor

assert multiplyBy(1) == 2
assert multiplyBy(1, 10) == 10

Written with Groovy 3.0.1.